Hubungan Fleksibilitas Kerja dan Budaya Organisasi dengan Kepuasan Kerja Driver Gojek Mataram - Made Arya Sudarsana; Cahyadi, Irwan (As-Syirkah: Islamic Economic & Financial Journal, 2026)
Job satisfaction is an important factor in maintaining performance, loyalty, and work sustainability in the online transportation sector. For Gojek drivers, work flexibility and organizational culture are assumed to influence job satisfaction due to the unique nature of their work, which combines independent working arrangements with organizational operational systems. This study aims to analyze the relationship between work flexibility and organizational culture toward job satisfaction among Gojek drivers in Mataram City, both partially and simultaneously. This research employed a quantitative approach using a survey method. The study involved 100 active Gojek drivers in Mataram City selected through purposive sampling. Data were collected using structured questionnaires and analyzed using correlation and regression tests at a 5% significance level. The results showed that work flexibility has a positive and significant relationship with job satisfaction (t = 2.819; p = 0.006). Organizational culture also has a positive and significant relationship with job satisfaction (t = 3.971; p = 0.000). Simultaneously, work flexibility and organizational culture show a significant relationship with job satisfaction (F = 28.606; p = 0.000).  An Adjusted R² value of 0.358 indicates that both variables contribute 60.9% to job satisfaction, while the remaining 39.1% is influenced by other factors outside the study. Regression coefficients further indicate that a one-unit increase in work flexibility raises job satisfaction by 0.208 units, while a one-unit increase in organizational culture raises job satisfaction by 0.802 units. In conclusion, work flexibility and organizational culture play a role in increasing job satisfaction among Gojek drivers in Mataram City. These findings suggest that the better the work flexibility and the more positive the organizational culture perceived by drivers, the higher their level of job satisfaction.